CAMPAIGN FOTOGRAFI STILL LIFE #OCEANFORLIFE DAMPAK BURUK SAMPAH PLASTIK PADA HEWAN LAUT: Campaign Still Life Photography #oceanforlife: The Negative Impact of Plastic Waste on Marine Animals - Aisyah, Salwa Suci; Novianti, Erlina; Aurelia, Silviana Amanda (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Campaign Still Life Photography #oceanforlife: The Negative Impact of Plastic Waste on Marine Animals. Indonesia ranks as the second-largest contributor of plastic waste into the ocean, which poses a serious threat to marine life. Plastic contaminated with microorganisms from the plastisphere is often misinterpreted as food by marine animals, endangering the ecosystem. This research aims to raise public awareness about the importance of keeping the ocean clean and protecting marine animals. The author employs a still life photography approach in this campaign to illustrate the negative impacts of plastic waste. A practice-based research method is chosen, where the creative process of photographing and selecting props serves as the primary tools for conveying the message. The result is a collection of five still life photographs that effectively communicate the campaign's message. Still life photography proves to be a powerful visual approach for voicing environmental issues without the need for direct interaction with the ocean